Smartphone Addiction among Students and its Consequences - Normurodov, Hazratova Hulkar; qizi, Rizamamatova Gulsanam Rifat (American Journal of Biodiversity, 2025)
This article analyzes the relationship between smartphone addiction and sleep quality among students. Based on scientific sources, it is highlighted that excessive use of smartphones negatively affects not only the learning process but also physical health, psychological well-being, and social life. It is particularly emphasized that using a phone in the evening reduces the secretion of the sleep hormone melatonin, disrupts biological rhythms, and lowers sleep quality. Research findings indicate that excessive screen time can lead to eye strain, sleep deprivation, anxiety, depression, and reduced social activity. Therefore, it is recommended that students regulate their daily screen time, limit phone use during classes, and pay more attention to physical activity and face-to-face social interactions.